2021
DOI: 10.1111/icad.12479
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the blue spectrum of artificial light at night minimises insect attraction in a tropical lowland forest

Abstract: 1. New infrastructure development in previously natural environments is introducing light pollution to habitats at an unprecedented rate, which has the potential to be devastating for native insect assemblages.2. We evaluated insect attraction to three lamp types emitting different spectra of light (white, yellow-filtered and amber-filtered 3000 K LED lamps) and an unlit control in a lowland forest site in the northern Peruvian Amazon previously naïve to artificial illumination.3. Lamp type was the only variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 53 publications
(90 reference statements)
0
17
0
5
Order By: Relevance
“…This is worrying, given the current shifts in outdoor lighting technologies toward white LEDs ( 21 , 34 ). Yet, LEDs can be modified more easily than sodium lamps by adjusting their intensity (dimming) and spectral output (custom colors and filters) ( 38 , 63 , 64 ), offering the opportunity to minimize the negative impacts on insect populations, and linked ecosystem processes, at marginal costs.…”
Section: Discussionmentioning
confidence: 99%
“…This is worrying, given the current shifts in outdoor lighting technologies toward white LEDs ( 21 , 34 ). Yet, LEDs can be modified more easily than sodium lamps by adjusting their intensity (dimming) and spectral output (custom colors and filters) ( 38 , 63 , 64 ), offering the opportunity to minimize the negative impacts on insect populations, and linked ecosystem processes, at marginal costs.…”
Section: Discussionmentioning
confidence: 99%
“…Although lighting professionals (e.g., design and industry) increasingly acknowledge ALAN as a threat to biodiversity, there are diverging views regarding potential obstacles to light pollution mitigation (Schulte-Römer et al, 2019;Pérez Vega et al, 2021). Current technological advancements in outdoor lighting, particularly LEDs, in principle allow developing lighting mitigation strategies that balance conflicting interests between humans and biodiversity, but this potential remains largely untapped (Longcore, 2018;Bolliger et al, 2020;Deichmann et al, 2021;Jägerbrand and Bouroussis, 2021). Furthermore, LEDs are an energy efficient technology that promises net savings in energy consumption.…”
Section: Bending the Curve Of Biodiversity Lossmentioning
confidence: 99%
“…It distracts or disorientates either the courtship partners or simply reduces the efficacy of communication by flooding the background with illumination thereby decreasing the signal to noise ratio. Deichmann et al [48] suggested that switching to lights of longer wavelength in order to minimize the adverse effects on majority of insects in turn attract bioluminescent insects thereby posing threat to their survival. Langevelde et al [49] studied the effect of artificial light on feeding behavior of moths.…”
Section: Pollutionmentioning
confidence: 99%